2009
DOI: 10.1002/ijc.24272
|View full text |Cite
|
Sign up to set email alerts
|

Alpha fetoprotein is a novel protein‐binding partner for caspase‐3 and blocks the apoptotic signaling pathway in human hepatoma cells

Abstract: Although there is increasing evidence that alpha fetoprotein (AFP) may function as regulatory factor in the growth of tumor cells, the precise mechanism is still unclear. In the current study, we investigated the role of the cytoplasmic AFP in caspase-3-mediated signaling of apoptosis. Our results showed that low doses of TNF-related apoptosis-inducing ligand (TRAIL) elevated the activity of caspase-8, but not caspase-3. Caspase-3 colocalized and interacted with AFP in the cytoplasm of Bel 7402 cells, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 36 publications
(43 reference statements)
4
124
0
1
Order By: Relevance
“…The precise mechanism by which AFP affects prognosis remains unclear. However, several studies have reported that AFP is a novel protein-binding partner for caspase-3, which blocks the apoptotic signaling pathway, and promotes the growth of human hepatoma cells as a co-repressor in retinoic acid (RA)-RA receptor signaling (40,41). Therefore, the low AFP level was independently associated with better OS.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which AFP affects prognosis remains unclear. However, several studies have reported that AFP is a novel protein-binding partner for caspase-3, which blocks the apoptotic signaling pathway, and promotes the growth of human hepatoma cells as a co-repressor in retinoic acid (RA)-RA receptor signaling (40,41). Therefore, the low AFP level was independently associated with better OS.…”
Section: Discussionmentioning
confidence: 99%
“…AFP is widely used as a biomarker for HCC diagnosis, monitoring, and follow-up, but studies of its biological function have only recently increased. Numerous studies confirmed that AFP has complicated biological functions, such as promoting liver cancer cell proliferation, inhibition of apoptosis, and immune evasion (Li et al, 2009;Coumar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that AFP plays an important role in cell proliferation and apoptosis of HCC (Yang et al, 2008;Li et al, 2009). Survivin is a recently discovered member of the apoptosis inhibitor protein family that is expressed in a variety of tumors but remains silent in normally differentiated tissues.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above in inflammation during pregnancy, AFP has been reported to interact and bind to caspase-3,9 enzymes (cysteine proteases) which constitute key components of molecular complexes called inflammosomes [34,79]. These inflammation-induced organelles are multiprotein oligomer formations that enhance inflammatory processes leading to cell death [80].…”
Section: Afp and Autoimmune Neuroinflammationmentioning
confidence: 97%
“…The combination of elevated AFP together with elevated ICAM-1 levels were correlated with pre-term birth, intrauterine growth retardation (IUGR), and prematurity [32]. AFP is known to bind to caspases; such agents are activated to mediate proteolytic processing of proinflammatory cytokine IL-1β, levels of which are elevated in some forms of preterm birth and maternal metabolic disorders [33,34].…”
Section: Afp and Inflammation During Pregnancymentioning
confidence: 99%